HIGH PERFORMANCE LIQUID CHROMATOGRAPHIC METHOD DEVELOPMENT AND VALIDATION FOR THE SIMULTANEOUS DETERMINATION OF GALLIC ACID AND BETA SITOSTEROL IN AMPELOCISSUS LATIFOLIA (ROXB.) PLANCH - A. Pednekar, Parag; Kulkarni, Vanita; Raman, Bhanu (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: A simple and accurate Reverse phase High Performance Liquid Chromatographic method was developed for simultaneous determination of Gallic acid and Beta sitosterol in methanolic soxhlet leaf extract of Ampelocissus latifolia (Roxb.) Planch. Methods: The separation was achieved using a Surveyor HPLC system (Agilent 1100 series) equipped with U.V. detector. The Column used for Method development and validation was Kromasil 100-5C18 (250x 4.6, 5Î¼m) as stationary phase with a mobile phase comprising of Acetonitrile: Water (95:05) v/v at a flow rate of 1.0 ml min-1 and UV detection at 195 nm with a run time of 10.0 min at 300C. Results: Regression equations showed good linear relationships (Correlation coefficient r = 0.9969 for Gallic acid & 0.9979 for Beta sitosterol) between the peak area of each marker and concentration. The assay was reproducible with overall intra and inter-day precision. The method has been developed and validated for simultaneous detection of the Gallic acid and Beta sitosterol in methanolic soxhlet leaf extract of Ampelocissus latifolia. Conclusion: The validated method gave good results of system suitability, linearity, LOD & LOQ, precision (Intra-day & Inter-day), accuracy & robustness. The validated HPLC method can be used for a routine quality control analysis. Â KEY WORDS HPLC, Gallic acid, Beta sitosterol, Ampelocissus latifolia (Roxb.) Planch.